Compact configurations of hexagonal microstrip antennas. Issue 3 (28th January 2013) - Ray, K. P.; Pandey, M.D.; Rashmi, R.; Duttagupta, S. P.
Abstract This article proposes compact configurations of hexagonal microstrip antennas (HMSA). The hexagonal microstrip antenna is modified by shorting along the zero potential line, perpendicular to the feed axis resulting in shorted half‐hexagonal and quarter‐HMSA for the two feed configurations along X and Y axes. The fundamental principle is to keep the field distribution same so that the resonance frequency remains unaltered while achieving a compact footprint. The area reduces by a factor of four, for the quarter patch, while maintaining approximately the same resonance frequency. © 2012 Wiley Periodicals, Inc. Microwave Opt Technol Lett 55:604–608, 2013; View this article online at wileyonlinelibrary.com. DOI 10.1002/mop.27396